Automatic generation of locally refined Cartesian meshes: Data management and algorithms - Capizzano, Francesco (International journal for numerical methods in engineering, 2018)
Summary The paper describes the main features of an automatic and three‐dimensional Cartesian mesher specifically designed for compressible inviscid/viscous flow solvers based on an immersed boundary technique. The development of a meshing tool able of conducting non‐isotropic cell refinements is a very tiresome task. The major difficulty is to imagine, at the pre‐design phase, a light but flexible data management, which minimizes the memory and CPUs' resources. In particular, the embedded geometry has to be detected by means of a fast and robust tagging procedure. Cells in proximity of the wall have to be refined in a proper way to adequately solve large flow gradients. Smooth variation of mesh density between differently refined zones has to be guaranteed to increase the flow solver robustness. A procedure to obtain accurate data on the geometry surfaces should be foresee. Here, a robust algorithm is developed to reconstruct a surface triangulation starting from the intersection points among volume cells and the geometry surfaces. The paper attempts to address all the above issues to help the readers in designing their own tools and suggesting them a way forward.